PERAN SISTEM INFORMASI AKUNTANSI DALAM PEMBUATAN KEPUTUSAN MANAJEMEN - Faqihudin, M. (PERMANA, 2010)
Decisions related to something in the future so that faced with various alternatives to the uncertainty that accompanies it. Decision makers need accurate and valid information to anticipate them. There are a lot of information that can be used, one of which is Accounting Information System is the system used to process data and transactions to provide information needed by the user to plan, control and operate thebusiness. Keywords: Decision Making, Accounting Information Systems